Data appendix to the behavior of LNG vapor clouds: wind-tunnel tests on the modeling of heavy plume dispersion: final report (July 1979-September 1981) - Neff, D. E., author; Meroney, R. N., author; Fluid Mechanics and Wind Engineering Program, Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1982)
Visual and concentration measurements were made for a large number of continuous ground-level releases of heavy gases into a wind-tunnel boundary layer. These different plumes were not affected by any topographic or building wake influences. The experiments provided a broad coverage of the variable range of source gas specific gravity, source gas flow rate, and approach flow wind speed. From an investigation of the physical similarity between plumes, the permissible modeling distortion in source density, volume flux ratio, and length scale ratio was quantified. The concentration scaling theory which was previously limited to far-field behavior was extended to cover the entire range of plume concentrations. Generalized behavior models were constructed from the laboratory tests. These models were scaled up to atmospheric conditions. The range of atmospheric scenarios to which these laboratory data are applicable is summarized. Measurements on the behavior of transient dense plumes were also obtained.
CER81-82DEN-RNM25.
March 1982.
Accompanying final report has title: The behavior of LNG vapor clouds: wind-tunnel tests on the modeling of heavy plume dispersion: final report, July 1979-September 1981.
Keywords: Wind tunnel models; Liquefied natural gas -- Fluid dynamics